Creativity, Pluralism, and Fictitious Narratives: Understanding IP Law Through Karl Polanyi - Suthersanen, Uma (2022)
For over a century, jurists have debated as to whether IP rights should be extended to this or that output such as photographs, computer programs, products of data aggregation, virtual objects, natural and organic materials, “creative” algorithms, and genes. What is surprising is the continuing and bifurcating discourse landscape: “IP law protects and rewards creativity” versus “IP law protects investment”. This paper suggests that IP law indiscriminately and simultaneously protected all sorts of res emanating from creative and entrepreneurial labour as well as from capital investment. Continued attempts to discuss or adjudicate IP law, policy and reform through strict conceptual silos such as creativity, labour, and investment are doomed narratives.Instead, I invite readers to appreciate that early modern rules in sensu lato were about mixed motivations of reward, investment, recognition, competition, honour, public interest, and more. The implicit suggestion in this paper is that the root cause of continuing legal conundrums today is the failure to appreciate the pattern set out by two related socio-legal mappings: (i) motivations for early rules in relation to creative and entrepreneurial labour and products in Europe; and (ii) the extent to which current IP norms and laws evolved to absorb such myriad motivations over five hundred years. I employ Karl Polanyi’s theory on the commodification of labour, including investment-backed labour, into tradeable, fictitious commodities, where law and property are recognised as vital institutional tools which disembed and re-embed society from/into the economy. Polanyi’s motivation ethos is effective in synthesising the different mapping points to create a pointilliste landscape which, in turn, shows why IP law only makes juridical sense if it is viewed as a pluralistic concept.
Keywords: creativity; intellectual property; pluralism

Pandemic Paradox and Polanyi: Financial Markets Rise, Economies Crash, and Regulators Toss a Coin - Findlay, Mark (2020)
In the pandemic, investors like all responsible citizens share an obligation to keep the community safe. This obligation extends to informed market decision-making which goes beyond self-interest. The current disconnect between financial markets and the economy is a story of two different realities – or perhaps one harsh reality and one expectant gamble. The disconnect cannot just be explained by the different purposes of economic and financial market analysis but rather by the information indicators on which these rely. To forewarn regulators concerned that these two worlds of global wealth generation and growth moving to polar opposite futures, this brief review has these aims:• To reflect on a legal model for financial markets, their regulation and its limitations so that law and finance may be understood as positively relational when considering market sustainability; and then• To suggest that the explanation for this dangerous disconnect can be found in Karl Polanyi’s understanding of fictitious commodities in self-regulating markets, dis-embedding from the social and his propositions for market correction through the double movement.Despite the neoliberal logic to the contrary (where financial markets are deemed only for maximising investor/shareholder profit) financial market regulation should prioritise market sustainability as part of pandemic control policy.
Keywords: disconnect; economy; financial markets; market sustainability and resilience; pandemic crisis; responsible market decision-making